Synthesis, Characterization and Biological Activity of ONO Donor Schiff Base and its Metal Complexes - Nalini, R.; Basavarajaiah, S.M.; Yernale, N.G.; Ramakrishna Reddy, K. (Asian Journal of Chemistry, 2022)
A new Schiff base ligand (E)-2-((7-hydroxy-4-methyl-2-oxo-2H-chromen-8-yl)methylene)-N-(5-methyl-3-phenyl-1H-indol-2-yl)hydrazine carboxamide (L) (3) was synthesized by the reaction of N-(5-methyl-3-phenyl-1H-indol-2-yl)hydrazinecarboxamide (1) and 7-hydroxy-4-methyl-2-oxo-2H-chromene-8-carbaldehyde (2). The Cu(II), Co(II), Ni(II) and Zn(II) metal complexes (4a-d) were synthesized and its structural elucidation was done by different spectral techniques. The Schiff base (3) behaves as ONO donor ligand and forms the complexes of the sort [M(L)(Cl)(H2O)2] for Cu(II) (4a) and Zn(II) (4d) and [M(L)2] for Co(II) (4b) and Ni(II) (4c). Compounds (3) and (4a-d) were tested in vitro for antimicrobial action, cytotoxicity property against Artemia salina and anti-tuberculosis assay against Mycobacterium tuberculosis (ATCC 25177). The metal complexes showed very good biological activity.